ANALISIS STRATEGI GURU DALAM MENANGANI SISWA LAMBAN BELAJAR (SLOW LEARNER) KELAS IV DI SDN 2 KURIPAN SELATAN LOMBOK BARAT: Penelitian Kualitatif - Suci Ramdani, Lia; Kemala Dewi, Nurul; Puji Astria, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers' strategies in handling slow learner students in Grade IV at SDN 2 Kuripan Selatan, It focuses on teachers' strategies in classroom management, motivating slow learners, and treating slow learners in the classroom. This research employs a descriptive qualitative approach. The subjects of this study are the fourth-grade teacher and two slow learner students. Data collection techniques include interviews, observations, and documentation. Data analysis follows the Miles and Huberman model, which consists of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that teachers use the following strategies to handle slow learners: 1) classroom management strategies, which involve arranging the seating position of slow learners. Their seats remain unchanged and are always placed in the back row. The teaching methods commonly used for slow learners include lectures, demonstrations, question and answer sessions, and assignments. Teachers utilize learning media such as laptops and LCD projectors to display power point presentations or educational videos in the form of cartoons, animations, and colorful images. 2) strategies to motivate slow learners, including providing various forms of emotional support, such as praise, applause, and positive affirmations. 3) strategies for treating slow learners, which involve giving special treatment such as repeating learning materials, using easily understandable language, guiding students in completing assignments, and providing additional time to complete tasks.